PENGARUH SOSIALISASI PAJAK, TARIF PAJAK, PENERAPAN PP NO. 23 TAHUN 2018, DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK (Studi Empiris pada Wajib Pajak UMKM di Kabupaten Sampang) - Rika Noviana; Afifudin Afifudin; Hariri Hariri (Universitas Islam Malang, 2020)
The purpose of this study was to determine the effect of Tax Socialization, Tax Rates, Application of PP Number 23 Year 2018, and Tax Sanctions Against UMKM Taxpayer Compliance in Sampang Regency. The research method used in this study is a quantitative research method. This study uses primary data obtained through questionnaires. Data analysis method used is multiple linear regression analysis. The sample in this study is taxpayers UMKM registered at the Sampang Regency Cooperative UKM Office. The number of samples in this study were 95 UMKM.The results showed that simultaneously, the variable of Tax Socialization, Tax Rates, Application of PP No. 23 of 2018, and Tax Sanctions have a positive and significant effect on the Compliance of UMKM Taxpayers in Sampang Regency. While partially, the variable of Tax Socialization, Tax Rates, and Tax Sanctions does not affect the Compliance of UMKM Taxpayers in Sampang Regency, but the Application of PP No. 23 of 2018 has a positive and significant effect on the compliance of UMKM taxpayers in Sampang Regency. Keywords : Tax Socialization, Tax Rate, The Application of Government Regulation Number 23 of 2018, Tax Sanctions, and Taxpayer Compliance.